2019
DOI: 10.1007/s00726-019-02747-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact of PTMs on the protein backbone conformation

Abstract: Post-Translational Modifications (PTMs) are known to play a critical role in the regulation of the protein functions. Their impact on protein structures, and their link to disorder regions have already been spotted on the past decade. Nonetheless, the high diversity of PTMs types, and the multiple schemes of protein modifications (multiple PTMs, of different types, at different time, etc) make difficult the direct confrontation of PTM annotations and protein structures data.We so analyzed the impact of the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
(94 reference statements)
1
18
0
Order By: Relevance
“…Examples of glycans as components of glycosylated proteins are the N -glycans [ 3 ] and O-glycans [ 4 ] attached to glycoproteins and the glycosaminoglycans attached to proteoglycans [ 5 ]. Experimental atomic-resolution structural biology on glycosylated proteins is complicated by the non-template based synthesis of the attached glycans [ 6 ], which precludes a convenient source of homogeneous sample from biological sources, the intrinsic flexibility of glycans, which hinders conformational analysis by X-ray crystallography and NMR spectroscopy [ 7 ], and the covalent linkage of proteins with glycans, which can affect the structural properties of both the glycan and protein components [ 8 , 9 , 10 ]. In the context of membrane proteins, experimental atomic-resolution structural biology using X-ray crystallography entails extracting the membrane protein from its native lipid environment in order to create protein crystals [ 11 ], which means the effects of natural glycolipids in the native bilayer are not included in the structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of glycans as components of glycosylated proteins are the N -glycans [ 3 ] and O-glycans [ 4 ] attached to glycoproteins and the glycosaminoglycans attached to proteoglycans [ 5 ]. Experimental atomic-resolution structural biology on glycosylated proteins is complicated by the non-template based synthesis of the attached glycans [ 6 ], which precludes a convenient source of homogeneous sample from biological sources, the intrinsic flexibility of glycans, which hinders conformational analysis by X-ray crystallography and NMR spectroscopy [ 7 ], and the covalent linkage of proteins with glycans, which can affect the structural properties of both the glycan and protein components [ 8 , 9 , 10 ]. In the context of membrane proteins, experimental atomic-resolution structural biology using X-ray crystallography entails extracting the membrane protein from its native lipid environment in order to create protein crystals [ 11 ], which means the effects of natural glycolipids in the native bilayer are not included in the structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has been observed that disorder‐to‐order transition could be induced by the modifications of phosphor‐serine/‐threonine, mono‐/di‐/tri‐methyllysine, sulfotyrosine, 4‐carboxyglutamate, and potential 4‐hydroxyproline 214 . By investigating the relationship between PTMs and the local backbone conformation changes of modified residues, it is indicated that PTMs could either stabilize or destabilize the backbone structure, at a local and global scale, depending on the PTM types 215 . For example, by comparing with the structures of unmodified cyclin‐dependent kinase 2 (CDK2), phosphorylation at Thr160 would rigidify (potential stabilization) the backbone (lower Neq and lower B‐factor) locally yet increase the deformation (potential destabilization) of two other regions, near Tyr14‐Tyr15, and near Tyr39, three other phosphorylation sites related to CDK2 activity and subcellular localization, respectively.…”
Section: Targeting Ptm Protein Isoforms In Drug Designmentioning
confidence: 99%
“…With the rise of ML, new algorithms or methods have been used to study macromolecular dynamics along with MD simulations, 300–303 allowing the deep mining of MD data for better understanding of protein dynamics. Structural analysis has demonstrated that different PTM types can either stabilize or destabilize the backbone of the protein locally or globally 215 . ML is known for its capability of capturing the hidden pattern and therefore it will help uncover the structural changes induced by PTMs along with MD simulations or other computational methods.…”
Section: Potential Directions Of Targeting Ptm Isoforms In Drug Discomentioning
confidence: 99%
“…Modifications (Craveur et al, 2019), KISS1R (Chevrier et al, 2013), and in NMDA Receptor Channel Gate (Ladislav et al, 2018). Besides, it has also been used with experimental data (Schneider et al, 2014a;Schneider et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%